Changes in Immunological Parameters in Patients Treated Using Direct and Indirect Restorations of the Hard Tissues of the Anterior Teeth in Combination with an Antioxidant - Iryna R. Kumhyr1 , Volodumyr P. Levko1 , Zinovii R. Ozhogan2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The problem of aesthetic restoration of the hard tissue defects in the anterior teeth and the choice of materials for quality restorations, which can include direct composite or indirect ceramic restoration, in particular ceramic veneers, is currently extremely important in clinical dental orthopedics. Currently used composite and ceramic materials are known to have different effects on the conditions of the marginal periodontium and the local immunity in the oral cavity. Therefore, we propose a new approach to treatment, which is the use of indirect ceramic restorations in combination with an antioxidant. The purpose of this article is to increase the effectiveness of treatment in patients with defects in anterior teeth using indirect ceramic restorations with antioxidants. To study the intensity of immune reactivity in patients with existing defects of the coronal part of the anterior teeth, we analyzed the levels of lysozyme and sIgA in the oral fluid. The results of the studies confirm the advantages of indirect ceramic restorations over direct composite ones in the treatment of hard tissue defects in the anterior teeth, taking into account the levels of immunological reactivity and using an antioxidant drug Resverasin.